Potential of natural clay derived functionalized adsorbents for effective remediation of sanitary landfill leachate - Asri, Muhamad Aniff Ahmad (Pusat Pengajian Kesihatan, 2015)
This study investigated the preparation of natural based adsorbent clay via acid modification for the adsorptive removal of chemical oxygen demand (COD) and ammonical nitrogen from the semi-aerobic sanitary landfill leachate. The effect of adsorbent dosage, contact time and pH on the adsorption process were evaluated. The experimental results manifested that the adsorptive removal of COD and ammonical nitrogen increased with increasing the adsorbent dosage and contact time, recorded the adsorptive removal of COD and ammonical nitrogen of 71.93% and 68.94%, respectively, at the adsorbent dosage of 4.5 g/200 mL and pH 7. The experimental data were modelled using two isotherm models, namely Langmuir and Freundlich isotherm models. The adsorption equilibrium data were favourably fitted to the Langmuir isotherm model, with a maximum monolayer adsorption capacity for COD and ammonical nitrogen of 89.17 mg/g and 151.60 mg/g, respectively. The adsorption kinetic was tested using pseudo-first-order and pseudo-second-order kinetic models. The pseudo-second-order kinetic model was best described the adsorption of COD and ammonical nitrogen onto the acid-activated natural clay, with the coefficients of correlation, R2 for COD and ammonical nitrogen of 0.998 and 0.997, respectively. The result demonstrated that the prepared clay based adsorbent is highly feasible for the effective remediation of sanitary landfill leachate.